До проблем інституціонального забезпечення інноваційного розвитку вугільної галузі - Амоша, О.І.; Драчук, Ю.З.; Кабанов, А.І. (Економіка промисловості, 2015)
Розглянуто проблеми інституціонального середовища вугільного виробництва на інноваційній основі, що обумовлені інституціональними складовими: інституціями та інститутами з визначеними характерними ознаками диференційованого їх впливу на розвиток вугільної галузі. Рассмотрены проблемы институциональной среды угольного производства на инновационной основе, обусловленные институциональными составляющими: институциями и институтами с определенными характерными признаками дифференцированного их влияния на развитие угольной отрасли. For large-scale structural and innovative transformation the development of economy of Ukraine in modern conditions requires substantial strengthening of the relationship between elements of the innovation process through the establishment of institutional frameworks. This is especially true for the coal industry as it feels the significant impact of the institutional environment. The foundations for the formation of the institutional environment of innovative development of coal enterprises are considered. They are based on: identifying and disclosing the components of institutional support of innovative development of the coal industry: clarify the content of the institutional environment of innovative development of coal industry; determining the directions of formation of institutional support of innovative development of coal industry; trend changes in the institutional environment of innovative development of industry in Ukraine taking into account industry-specific; conceptual positions of institutional support of innovative development of coal industry; proposals for improving the organizational-economic mechanism of innovative development of coal production; systematization of factors of state regulation of innovative development of the coal industry based on market transformation processes in the economy Ukraine. To the base of the formation of institutional support of innovative development of coal industry the generalized approaches of scientific schools «economic security of industrial enterprise» due to classification features are in great importance as well as external and internal factors that reduce the level of economic security of enterprises, constituent elements of the institutional mechanism of economic security of industrial enterprise, consideration of the factors influencing the risks associated with the implementation of investment and innovation projects in the coal industry and measures to minimize their impact through the creation of innovative structures - technology parks. Research recommendations as to improve the regulatory and legal support of innovative development of the coal industry are given in general, and the Donbass coal area is currently in an emergency. The institutionalization of their activity the coal industry enterprises should carry on through the process of «investment» in different areas (human and productive capital, implementation of various social priorities, formation of the state policy of energy independence, etc.). To ensure the most positive outcomes of its social and industrial activity coal enterprises need to accumulate and efficiently manage not only significant material, financial, intellectual, human, and other resources, but also to focus on maintaining a high level of capitalization based on the optimization of different sources of capital.The problem of technical and technological modernization of coal mines is extremely urgent for overcoming the unprofitability and improving the efficiency of the domestic coal industry. This issue is of a particular relevance now, when the recovery of the coal industry in Ukraine is significantly complicated by the need to overcome the consequences of the fighting in the Donetsk and Lugansk regions.